PENGARUH LATIHAN VARIASI TERHADAP KEMAMPUAN PASSING BAWAH PERMAINAN BOLA VOLI SISWA EKSTRAKURIKULER PUTRA SMAN 1 KAMPAR UTARA - Ryan Saputra; Dedi Ahmadi; Vigi Indah Permatha Sari (Jurnal BOLA: Bersama Olahraga Laju Asia, 2023)
This research is based on observations in the field based on the fact that male extracurricular students at SMAN 1 Kampar Utara were not able to make bottom passes well. The aim of this research is to find out how much influence training variations have on the bottom passing ability of male extracurricular students at SMAN 1 Kampar Utara. This research method is an experimental method. The research was carried out at SMA Negeri 1 Kampar Utara in October 2023.The sample for this research was all male extracurricular students at SMAN 1 Kampar Utara, totaling 16 people.To measure your bottom passing ability by doing a 1 minute bottom passing test. The results of the research were that there was a significant effect of varied training on the bottom passing ability of male extracurricular students at SMAN 1 Kampar Utara.Thus, the results of this study can be concluded that variation training has a significant influence on the bottom passing ability of male extracurricular students at SMAN 1 Kampar Utara by 15.24 or 78.92%.